Fanakalo as a trade language in Kwazulu-Natal - Newby-Rose, Heidi (Stellenbosch : Stellenbosch University, 2011)
ENGLISH ABSTRACT: This study investigates the use of the pidgin Fanakalo as a trade language in rural KwaZulu-Natal: its birth under certain historical circumstances; its spread; its apparent growth, post-1990, as new immigrants continue to enter the country and acquire and use Fanakalo out of expediency; and the reasons why Fanakalo continues to thrive in certain contexts. It focuses specifically on similarities between the relations between Gujarati traders and their customers in the 19th century and the relations that exist between Gujarati and Pakistani traders and their Zuluspeaking customers today. Data was collected primarily through semi-structured interviews with nine Gujarati traders – two born in South Africa and the others recent immigrants – five Pakistani traders and ten Zulu speakers, of which two were employees of traders while the others were customers. The results of the data analysis suggest the principles of expediency and non-intimacy may provide a space where Fanakalo can continue to flourish. Pidgins are a neglected element in the study of intercultural communication and the study endeavours to provide pointers for further research in this field.